Length of stay is associated with incidence of in-hospital malnutrition in a group of low-income Brazilian children El periodo de hospitalización está asociado con la incidencia de desnutrición en un grupo de niños brasileños de bajo nivel socioeconómico. - Gilberto Kac; Patricia Camacho-Dias; Daniele Silva-Coutinho; Rosana Silveira-Lopes; Viviane Vilas-Boas A. Marins; Ana Beatriz V. Pinheiro (Instituto Nacional de Salud Pública, 2000)
OBJECTIVE: To test the hypothesis that increased length of stay and anthropometric status at admission are significant factors associated with in-hospital malnutrition (IHM). MATERIAL AND METHODS: Prospective study with two weight (admission and discharge) and one height (admission) measurements per child at the Instituto de Puericultura e Pediatria Martagão Gesteira (IPPMG), Rio de Janeiro, Brazil. The study included 456 children of low socioeconomic status under 10 years of age admitted to the IPPMG during 1997. Statistical analysis involved calculation of in-hospital malnutrition (IHM) prevalence by covariates. The length of hospital stay varied from 1 to 69 days. Association of IHM with gender, age category, length of stay, presence of wasting, and stunting, was tested by calculating odds ratios using multivariate logistic regression. RESULTS: Logistic regression showed that after adjusting for gender, age category, and presence of stunting at admission, presence of wasting at admission (OR= 0.07, CI 95% 0.01 - 0.55) and length of stay from 17 to 69 days (OR= 4.68, CI 95% 2.00 - 10.95), were statistically associated with IHM in the final model. CONCLUSIONS: As intervention measures, the authors suggest implementation of an early identification system for children at risk of developing IHM, along with a review and implementation of in-hospital feeding protocols. OBJETIVO: Verificar la hipótesis de que un periodo de hospitalización prolongado y el estado nutricional al ingreso son factores significativamente asociados con la desnutrición durante la hospitalización. MATERIAL Y MÉTODOS: Estudio prospectivo con dos mediciones de peso (al ingreso y al alta) y una medición de estatura (al ingreso) por niño, realizado en el Instituto de Puericultura y Pediatría Martagão Gesteira (IPPMG), Río de Janeiro, Brasil. El estudio incluyó 456 niños de bajo nivel socioeconómico menores de 10 años de edad, admitidos en el IPPMG durante 1997. El análisis estadístico incluyó cálculo de prevalencia de desnutrición intrahospitalaria conforme a covariables. El periodo de hospitalización varió de 1 a 69 días. El análisis estadístico consistió en el cálculo de razones de momios usando regresión logística multivariada, para probar la asociación entre la desnutrición intrahospitalaria y género, edad, periodo de hospitalización, presencia de emaciación y estatura baja para la edad. RESULTADOS: La regresión logística mostró que después de ajustar por género, edad y estatura baja para la edad al ingreso, la presencia de emaciación al ingreso (OR= 0.07, CI 95% 0.01 - 0.55) y el periodo de hospitalización de 17 a 69 días (OR= 4.68, CI 95% 2.00 - 10.95) resultaron estadísticamente asociados con desnutrición intrahospitalaria en el modelo final. CONCLUSIONES: Como medidas de intervención, los autores sugieren implementar un sistema precoz de identificación al ingreso de los niños con riesgo de desarrollar desnutrición intrahospitalaria, junto con una revisión e implementación de protocolos de alimentación hospitalaria.